La Crucifixion : iconographie et spatialisation des peintures murales entre le ixe et le début du xie siècle dans l’Occident chrétien - Julie Mercieca (Bulletin du Centre d’Études Médiévales d’Auxerre)
This study deals with the iconography of the Crucifixion on the mural paintings, which were produced between the 9th and the beginning of the 11th century in the Christian Latin Europe and its margins. Poorly represented in the Latin West until the middle of the 8th century, this theme displays gradually on various supports and through different technics from Carolingian period, at the same time as the iconography tends to be crystallized. Based on thirteen paintings, this study intends to analyse the Crucifixion both as a constructed image in order to make sense, and as a monumental art. Painted on the religious buildings’ walls, the Crucifixion sometimes seats in specific ritual times or devotional practices. It also contributes to the sacralisation of the household of God, thus testifying a transformation of the religious feeling towards the Passion and its representations.